A Competitive Framework for Mineral Beneficiation and Value Addition in Zimbabwe - Laisani, John; Dacosta, Francis Amponsah; Mulaba-Bafubiandi, Antoine F (International Journal of Membrane Science and Technology, 2023)
The development of mineral beneficiation and value addition has the potential to drive sustainable socioeconomic development in Zimbabwe. However, the country has been facing challenges in fully leveraging its mineral resources endowment for economic growth. This paper aims to address this issue by presenting a comprehensive framework for mineral beneficiation and value addition in Zimbabwe. The framework was developed using a mixed-methods approach that involved a literature review, stakeholder consultations, and data analysis. The objectives of the framework are to enhance mineral beneficiation and value addition, promote sustainable socioeconomic development, and create economic opportunities for local communities. The framework comprises a set of strategies and policies aimed at addressing the challenges facing the mineral sector, including inadequate infrastructure, limited technological capacity, and inadequate financing. The framework also emphasizes the need for stakeholder collaboration, human capacity building, and the adoption of environmentally sustainable practices. The paper concludes by highlighting the potential benefits of the framework, including increased employment, foreign exchange earnings, and overall economic growth, and calls for its adoption by policymakers and stakeholders in Zimbabwe.